Progress on the Function and Application of Thymosin β4 - Xing, Yuan; Ye, Yumeng; Zuo, Hongyan; Li, Yang (Frontiers in Endocrinology, 2021)
Thymosin β4 (Tβ4) is a multifunctional and widely distributed peptide that plays a pivotal role in several physiological and pathological processes in the body, namely, increasing angiogenesis and proliferation and inhibiting apoptosis and inflammation. Moreover, Tβ4 is effectively utilized for several indications in animal experiments or clinical trials, such as myocardial infarction and myocardial ischemia-reperfusion injury, xerophthalmia, liver and renal fibrosis, ulcerative colitis and colon cancer, and skin trauma. Recent studies have reported the potential application of Tβ4 and its underlying mechanisms. The present study reveals the progress regarding functions and applications of Tβ4.